Prevalence of Diabetes and Dyslipidemia in Hypertensive Young Adults in a Tertiary Care Centre in Nepal, a Cross Sectional Study - Sharma Lamsal, Kamal; Neupane, Keshab R; Acharya, Niranjan; Lamsal, Dinesh K; Karmacharya, Niraj; Paudel, Deepak; Paudel, Rajan; Sharma, Rabi P (Journal of Institute of Medicine Nepal, 2020)
Introduction Diabetes mellitus (DM) and lipid disorders (LD) in hypertensive patients are associated with increased risk of cardiovascular complications requiring close follow-up and more aggressive treatment. Hence, the present study was done to study the prevalence of diabetes and dyslipidemia in young hypertensive patients i.e. <40 years in a tertiary care hospital, Nepal. Methods This is a hospital based cross-sectional study carried out in Civil Service Hospital, Kathmandu. Study included 165 patients of <40 years who had hypertension, either newly diagnosed or undergoing antihypertensive treatment from September 2018 to September 2019. Blood pressure was measured two times on right upper arm in sitting position at interval of 30 minutes and the average was taken. Fasting Lipid Profile and Fasting Blood Glucose was measured after 12 hours of fasting and the prevalence of dyslipidemia and diabetes were analyzed from the data collected. All calculations and statistical analyses are processed by the SPSS 25.0. Results Among 165 patients included, majority of patients, 107 (64.8%) were among 31-39 years, followed by 53 (32.1%) patients among 21-30 years. In total, 98 (59.4%) were male and 67 (40.6%) female. The prevalence of diabetes was 24 (14.5%) and pre-diabetes was 49 (29.7%). The prevalence of dyslipidemia was 125 (75.6%), high triglyceride being the most common disorder followed by low HDL in 87 (52.1%). Elevated total cholesterol was found in 53 (32.1%) patients and 48 (29%) had high LDL cholesterol level. Conclusion A high prevalence of diabetes, pre-diabetes and dyslipidemia was observed in the hypertensive patients <40 years of age.